[OP.4A.07] THE IMPACT OF BLOOD PRESSURE VARIABILITY ON ADVERSE OUTCOMES AFTER KIDNEY TRANSPLANTATION. (September 2016) - Pagonas, N.; Seibert, F.; Bauer, F.; Markakis, K.; Seidel, M.; Zidek, W.; Kykalos, S.; Klein, T.; Viebahn, R.; Westhoff, T.
Abstract : Objective: Elevated long-term blood pressure variability has been shown to be predictive of adverse outcomes in patients with chronic kidney disease. In kidney transplant recipients a negative correlation between endothelial function and short-term variability has been found. No data exist, however, for associations of visit-to-visit variability (long-term variability) and outcomes after kidney transplantation. Design and method: 877 patients who underwent kidney transplantation at the Charité-Universitätsmedizin Berlin and at the Universitätsklinikum Knappschaftskrankenhaus Bochum, Germany were included in this retrospective study. Patients were followed up for at least 12 months (up to 266 months) after transplantation. Visit-to-visit blood pressure variability over the first 12 months after transplantation (3 visits) and during the first 120 months after transplantation (7 visits) was calculated as the coefficient of variation (CV) = standard deviation (SD)/ mean blood pressure. Results: Patients were categorized to those with low vs. high level of systolic CV at 12 months, defined by the median value (CV < 5.6 and CV> = 5.6%). After adjustment for gender, age and mean creatinine over the first 12 months the combined endpoint of death or graft loss did not differ between the two groups (HR (95% CI) = 1.1 (0.82 – 1.56), p = 0.44). No association was also found between patients with low and high systolic CV over 120 months (p = 0.15). Only primary graft function was associated with better outcomes after transplantation (p < 0.001). Conclusions: Visit-to-visit blood pressure variability is not associated with mortality or graft loss after kidney transplantation in this retrospective analysis. The presence of primary graft function was predictive of better long-term outcomes after transplantation. Figure. No caption available.